PERAN DUKUNGAN SOSIAL TERHADAP PERTUMBUHAN PASCA TRAUMA: STUDI META-ANALISIS - M. L. Anantasari (University of Merdeka Malang, 2011)
abstract The meta-analysis review aimed to examine the role of social support on contributing to posttraumatic growth. The result of meta-analysis of 22 effect sizes from 3435 subject showed that social support moderately related to posttraumatic growth (r = 0,296). The difference in variance of correlation can be caused by sampling error (35%) and error in measurement of independent as well as dependent variable (1,21%). Keywords : Meta-analysis, Social Support, Posttraumatic Growth